PENYELESAIAN PERKARA PIDANA MELALUI NILAI KEARIFAN LOKAL MASYARAKAT INUMAN DALAM RANGKA OPTIMALISASI TUJUAN PEMIDANAAN - Ferawati Ferawati; Erdianto Erdianto; Tengku Arif Hidayat (Riau Law Journal, 2023)
AbstractThe use of the modern criminal justice system as a means of distributing justice has proven to encounter many obstacles, one of the contributing factors is because modern justice is loaded with the burden of formalities, procedures, bureaucracy and strict methodologies and the same process is still being carried out for all types of problems. obtained by modern society is nothing but bureaucratic justice, while the legal goals achieved are only legal certainty. This is very contrary to the wishes of the people who crave substantial justice. Through this study, researchers explore the values of local wisdom of the people in Inuman, Kuantan Singingi Regency, which are often used as an alternative for resolving criminal cases outside formal courts. The researcher hopes that the results of this study will be input for law enforcement officials in resolving cases, so that the sanctions imposed are not only useful for the perpetrators, but more importantly useful and beneficial for the recovery of victims' suffering or losses, which is also expected to better heal victims. and more resolution. Thus, the termination of conflicts or disputes, especially in criminal cases, can be carried out without any party losing face (elegant solution).  AbstrakPenggunaan sistem peradilan pidana modern sebagai sarana pendistribusi keadilan terbukti menjumpai banyak hambatan, salah satu faktor penyebabnya adalah dikarenakan peradilan modern sarat dengan beban formalitas, prosedur, birokrasi dan metodologi yang ketat serta  masih dilakukannya satu proses yang sama bagi semua jenis masalah.. sehingga keadilan yang diperoleh masyarakat modern tidak lain adalah keadilan birokratis,sedangkan tujuan hukum yang dicapai hanyalah kepastian hukum saja. Hal ini sangat bertentangan dengan keinginan masyarakat yang mendambakan keadilan substansial. Melalui penelitian ini, peneliti mengeksplorasi nilai-nilai kearifan lokal masyarakat di Inuman Kabupaten Kuantan Singingi,yang sering dijadikan alternatif penyelesai perkara pidana diluar pengadilan formal. Peneliti berharap hasil dari penelitian ini akan menjadi masukan bagi aparat penegak